Morphological and pomological characteristics of wild pears in the northwestern part of the Bosnia and Herzegovina - Zavišić Nada; Đurić Gordana; Bosančić Borut (Agroznanje, 2017)
The aim of this research is to examine the morphological and pomological characteristics of the wild pear population in the northwestern part of Bosnia and Herzegovina with the purpose of allocating genotypes for breeding programs of varieties and rootstocks. During 2012 and 2013, the study of the wild pear characteristics was carried out on the localities of: Banja Luka, Manjača, Potkozarje and Kozara. This research included morphological characterization of vegetative organs and pomological characterization of the fruits of all the selected genotypes. The shape of leaves in all the examined genotypes was elongated. The study of wild pear populations in the Banja Luka region has shown that wild pears are characterized by mostly smaller fruits, rounded form, while a few genotypes had fruits of elongated and flattened shape. Fruit weight varied from 7.44 g to 21.47 g and 73% of genotypes had fruit weight of over 10 g.